Institutional Quality and Green Growth Nexus in Nepal: Evidence from Cointegration Analysis With A Structural Break - Gajurel, Ram Prasad; Ojha, Rita Parajuli; Niroula, Anil (Tribhuvan University Journal, 2025)
The greening economy is a growing body of research in recent academia. Experiencing green growth is the precondition of sustainable development and can be promoted by maintaining quality institutions, this paper attempts to examine the relationship between institutional quality and green growth in Nepal. This study employed Gregory-Hansen co integration with structural break test and residual based Engle-Granger co integration test with a time series spanning from 1996 to 2021 to examine the association among variables. After the co integration test, this study applied ordinary least squares (OLS) for long-run and error correction mechanisms (ECM) for short-run dynamics with a break dummy series referencing 2005. The results revealed that there was a long-run association among variables with the existence of structural breaks. The OLS and ECM highlighted the negative impact of institutional quality on green growth in Nepal. Similarly, financial development negatively and trade openness positively impacted green growth in both the short and long run. On the flip side, findings indicated that electricity access could not influence green growth significantly in Nepal. Overall findings thus demonstrate the existing institutional quality may not be sufficient to promote green growth in Nepal. Moreover, the findings offer insights for policymakers to enhance institutional quality, promote green finance and technology, encourage green agriculture and indigenous techniques, and adopt renewable energy to support green growth, enforce environmental standards, and mitigate carbon emissions for sustainable economic development in Nepal.